Hypertension and erectile dysfunction: The role of endovascular therapy in Asia - Wang, Tzung‐Dau; Lee, Chih‐Kuo; Chia, Yook‐Chin; Tsoi, Kelvin; Buranakitjaroen, Peera; Chen, Chen‐Huan; Cheng, Hao‐Min; Tay, Jam Chin; Teo, Boon Wee; Turana, Yuda; Sogunuru, Guru Prasad; Wang, Ji‐Guang; et al. (The journal of clinical hypertension (Greenwich, Conn.), 2021)
The prevalence of erectile dysfunction (ED) is above 40% in both Asian and non‐Asian male populations after the age of 40 years. The prevalence of ED among hypertensive patients is approximately double than that in normotensive population. Pelvic arterial insufficiency is the predominant cause of ED in men aged over 50 years. Stenosis in any segment of the iliac–pudendal–penile arterial system, which is considered an erectile‐related arterial axis, could lead to ED. Pharmacotherapy with lifestyle modification is effective in alleviating sexual dysfunction, yet a substantial number of patients still develop ED. Given the established applicability of angioplasty for the entire iliac–pudendal–penile arterial system, penile duplex ultrasound, and pelvic computed tomography angiography could be considered as the routine screening tools in ED patients with poor response to phosphodiesterase‐5 inhibitors. Endovascular therapy for pelvic arterial insufficiency‐related ED has been shown to be a safe and effective treatment option in patients who have anatomically suitable vessels and functionally significant stenoses. Clinical improvement was achieved in over 60% of patients at one year following pelvic angioplasty in the PERFECT registry from Taiwan. A 30%‐40% restenosis rate in distal internal pudendal and penile arteries remains a hurdle. Angioplasty for pelvic arterial occlusive disease could be considered as a viable approach to arteriogenic ED.